Functional analysis of the p10 gene 5' leader sequence of the Autographa californica nuclear polyhedrosis virus. - Weyer, U (1988)
Deletions were made in the 5' non-coding (leader) sequence of the Autographa californica nuclear polyhedrosis virus (AcNPV) p10 gene which progressively removed nucleotides upstream from the ATG translation initiation codon. The effect of these deletions on p10 gene expression was studied using a transient expression assay. Fragments containing the putative promoter and the entire or partly deleted 5' leader sequence of the p10 gene were inserted in front of the chloramphenicol acetyltransferase (CAT) gene in the pSVO-CAT construct. Transfection of AcNPV-infected Spodoptera frugiperda cells with these plasmids resulted in higher CAT expression with increasing representation of the 5' leader sequence. The lowest level of CAT expression was found with a construct containing only 10% of the 5' leader sequence, but this was enhanced on average by 50-fold if the entire 5' leader sequence was retained. The results indicate that the entire 5' leader sequence of the p10 gene is necessary for the high level of expression. The normal transcription initiation site was utilized in the transient expression of CAT. The data are discussed in relation to the strong promoter of the baculovirus polyhedrin gene.